COVID-19 salgınının ekonomik ve sosyal etkilerinin azaltılması hakkında kanunun iş hukukuna yönelik hükümlerinin değerlendirilmesi* - Nazlı, Seçkin (İstanbul Medipol Üniversitesi, 2020)
Dünya çapında küresel salgın hastalık kabul edilen COVID 19 salgını ülkemizde de toplum sağlığı ve ekonomi üzerinde olumsuz etkiler yaratmıştır. Salgının olumsuz etkileri ile mücadele kapsamında 7244 sayılı Kanun kabul edilmiştir. Çalışmamızda 7244 sayılı Kanunun iş hukukuna ilişkin hükümleri ele alınmıştır. Özellikle işverenin fesih hakkının sınırlandırılması, ücretsiz izin ve nakdi ücret desteğine yönelik yasa hükümleri değerlendirilmiştir.

COVID 19 epidemic, which is accepted as a global epidemic, has had negative effects on public health and economy also in our country. Law No. 7244 was adopted within the scope of combating the negative effects of the epidemic. In our study, the effects of the provisions of Law No. 7244 regarding labor law were discussed. In particular, the provisions of the law regarding the limitation of the right of termination of the employer, unpaid leaves and the support of cash wage payments were evaluated.
Evaluation of the labor law related provisions of the code regarding to reduce the economic and social impacts of the COVID 19 epidemic
Keywords: İş Hukuku; Fesih Hakkının Sınırlandırılması; Ücretsiz İzin; Nakdi Ücret Desteği; Kısa Çalışma Ödeneği; Labor Law; Limitation of the Right of Termination; Unpaid Leaves; Support of Cash Wage Payments; Short-Time Working Allowance